The Christ of the miracle stories : portrait through encounter - Cotter, Wendy, 1946- (Peabody, Mass. : Baker Academic, 2010)
"Calling on her almost encyclopedic knowledge of conditions in the first-century Mediterranean world, Professor Cotter discusses the miracle stories reported in the Gospel of Mark in terms of the likely reaction of contemporary people upon seeing them or hearing of them. This enables her to portray the Jesus of these stories in terms of his divine authority and power and also as an example of how his followers are to treat those to whom they proclaim the gospel. The book is an excellent source for both historical information and theological reflection; Paul J. Achtemeier" -- BACK COVER.
Jesus and the leper (Mark 1:40-45) -- Jesus and Bartimaeus (Mark 10:46-52) -- Jesus and the friends of the paralytic (Mark 2:1-12) -- Jesus and the centurion (Q (Luke) 7:1, 3, 6b-9) -- Jesus and the Syrophoenician mother (Mark 7:26-30) -- Jesus and the father of a demonized boy (Mark 9:14-29) -- Jesus and his storm-tossed disciples (Mark 4:35-41) -- The sea-walking Jesus and his disciples (Mark 6:45-52).
Includes bibliographical references (p. ) and indexes.
Keywords: Jesus Christ -- Miracles; Jesus Christ -- Character; Jesus Christ -- Person and offices